2016
DOI: 10.1103/physrevb.93.024302
|View full text |Cite
|
Sign up to set email alerts
|

Origin of negative density and modulus in acoustic metamaterials

Abstract: This paper provides a review and fundamental physical interpretation for the effective densities and moduli of acoustic metamaterials. We introduce the terminology of hidden force and hidden source of volume: the effective density or modulus is negative when the hidden force or source of volume is larger than, and operates in antiphase to, respectively, the force or volume change that would be obtained in their absence. We demonstrate this ansatz for some established acoustic metamaterials with elements based … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 54 publications
2
56
0
Order By: Relevance
“…Clearly, the deformation concentrates in the pillar whereas it is almost zero in the plate. This is further supported by the flat branches in the low frequency edge of the gap that correspond to zero group velocities and are evidences of local resonances as widely documented in literature [21,[32][33][34].…”
Section: ∫∫∫ ∫∫∫supporting
confidence: 78%
“…Clearly, the deformation concentrates in the pillar whereas it is almost zero in the plate. This is further supported by the flat branches in the low frequency edge of the gap that correspond to zero group velocities and are evidences of local resonances as widely documented in literature [21,[32][33][34].…”
Section: ∫∫∫ ∫∫∫supporting
confidence: 78%
“…Since there are no plates in the x-direction, the effective density along the x-direction is considered as that of air22, and no loss is considered, i.e., ρ x  = 1.2 kg/m 3 . The bulk modulus is also assumed to be the same as air since it will not be altered by the thin plates2627. The setup for evaluating the complex effective density of the ADNZ metamaterial in the y-direction is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the system in figure 6(a), the interface is at n=5. Using the lattice parameters of the system in figure 6, we can calculate out the resonance frequency f in = ω/(2π) satisfying equation (22) as f in = 1.09 Hz. The penetration length of the interfacial evanescent wave is characterized by 1/κ from equation (20).…”
Section: Topological Interface Statesmentioning
confidence: 99%
“…The mass-spring structure with different coupling and spatial distribution can also have negative effective parameters [21][22][23][24][25][26][27] because of Bragg scattering and resonant mechanism in different frequency regimes. In 2007, following the work of [7], Milton and Willis proposed a mass-in-mass system and showed that the dynamic effective mass of composite materials, defined in the framework of Newtonʼs law of motion (contrary to the static gravitational mass), exhibits the existence of single or double negative properties [23].…”
Section: Introductionmentioning
confidence: 99%